Efektifitas Promosi Staycation Hotel Menggunakan Digital Marketing dalam Mempertahankan Tingkat Hunian Kamar di Masa Pandemi Covid-19 - Sofiani Sofiani (Destinesia : Jurnal Hospitaliti dan Pariwisata, 2022)
Product promotion is one of the methods used by companies that aim to break the sales of products that have been produced. Promotion is a way to inform, refer, and remind consumers directly or indirectly about a product or brand being sold (Fitri, 2016). In addition to increasing product sales, promotions also have certain objectives, namely to convey information, position the product, and provide added value from the product.Hotel Santika Indonesia makes staycation promotions as one of the superior products at all Santika Hotels in Indonesia. This product is expected to increase marketability during the COVID-19 pandemic which has reduced the room occupancy rate. With a promotion through good digital marketing, it will be able to increase the income of all Santika Hotels. By using digital marketing, namely through websites, social media, online advertising and mobile applications. By maximizing the four digital marketing segments, it will be able to lift promotions from renewal companies from various aspects, including following the latest news can be one of the attractions in carrying out promotional strategies through digital marketing.